Personalized approach of a hormonal contraceptive for patients requiring control of body weight (review) - T Yu Pestrikova; E A Yurasova (IP Berlin A.V., 2018)
Hormonal contraceptives are protected from undesirable pregnancy, but also have a row of other useful, uncontraceptive effects, both in regard to the reproductive system and all organism on the whole. An in this connection not insignificant role is executed by progestagens that is included in the complement of contraceptive. Drospirenone is enters in complement of a hormonal contraceptives, possesses to antimineralocorticoid activity, prevents to the delay of natrium and liquid in an organism, that supports stability of body weight, level of arterial pressure, prevents to sickly increase of mammary glands. Drospirenone renders an effect on the RAAS-system, similar spironolactone. Personalized approach of a hormonal contraceptive which contains of drospirenone is the mortgage of control of normal body weight, what is discussed in the article on the example of the drug Midiana.